Analisis dan Evaluasi Sistem Pengelolaan Sampah di Desa Pasirwangi : (Upaya Menuju Lingkungan Bersih dan Sehat) - Ima Siti Aminah; Az Zahroh Kamilatun Napsiyah; Rahayu Putri Gumilang; Fachrul Rozzy; Siska Ainul Guri; Aliyya Najma Zahira Achmad; Fathiyaturrohmah Fathiyaturrohmah; Siti Nur Yanah; Triana Suganda; Muhammad Gilang Permana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to analyze and evaluate the waste management system in Dusun 3, Pasirwangi Village, Pasirwangi Subdistrict, Garut Regency, which currently lacks both a landfill (TPA) and a temporary disposal site (TPS). As a result, residents are accustomed to improperly disposing of waste, including in the river, leading to environmental pollution. Through socialization efforts, a program for separating organic and non-organic waste was introduced. Organic waste is processed into liquid fertilizer using a mixture of organic waste, rice water, and sugar, which also produces magots that can be cultivated. Non-organic waste is repurposed into handicrafts. Additionally, trash bins were provided to improve disposal facilities. The results of the study show behavioral changes among residents in waste management, although not yet fully optimal. The evaluation highlights the need for more trash bins, increased environmental awareness, as well as the development of handicrafts from non-organic waste and magot cultivation as an economic resource. In conclusion, waste management in Dusun 3 has shown progress but still requires continuous improvement, especially regarding facilities and environmental education.